Penguatan Kesadaran Kesehatan tentang Risiko Konsumsi Gula Berlebih (Ultra-Processed Foods) di TK Hapakat Desa Bagendang Hilir: Sebuah Inisiatif Pendidikan Kolaboratif - Syahrul Mubaroq; Ajeng Cahyani; Linda Wati; Husnatun Zakiya; Yola Dwi Sukmawati; Alfit Ansari; Muhamad Samsul Sabirin; Novita Angraeni (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Excess sugar consumption, particularly from ultra-processed foods is a significant health issue for the community. This community service program aims to raise awareness about the health risks posed by excessive sugar consumption, with a focus on mothers in Hapakat Kindergarten, Bagendang Hilir Village. Through collaboration with the village Health Post, this activity was carried out with an educational approach in the form of socialization and interactive discussions. The methods used included material presentation, interactive discussion, questions and answers, and simulation of calculating daily sugar intake. The results of this activity showed an increase in participants' understanding of the dangers of excessive sugar consumption and preventive measures that can be applied in everyday life. This program is expected to contribute to government policies regarding preventive health education and regulation of sugar consumption in packaged food and beverage products.